Analysis of prognostic factors for pancreatic head cancer according to para‐aortic lymph node. (19th August 2016) - Lin, Jian‐yu; Zhang, Xing‐mao; Kou, Jian‐tiao; Fa, Hua; Zhang, Xin‐xue; Dai, Yang; He, Qiang
Abstract: This study was designed to investigate the relationship between prognosis of pancreatic head cancer and status of para‐aortic lymph node (PALN). A total of 233 patients with pancreatic head cancer who underwent surgical resection between February 2008 and October 2015 were enrolled in this study. Univariate and multivariate analyses were used to reveal the prognostic factors. Prognostic factors for patients with and without metastasis of PALN were analyzed, respectively. The 5‐year overall survival (OS) rate was 19.0% for all patients, and the positive rate of PALN metastasis was 18.9% (44/233). The 1‐, 2‐, 3‐, and 5‐year OS rates in patients without metastasis of PALN were 79.4%, 54.8%, 36.4%, and 22.9%, respectively, whereas the 1‐, 2‐, and 3‐year survival rates were 54.0%, 14.8%, and 0%, respectively, in patients with metastasis of PALN. Preoperative CA19‐9 level, tumor size, T status, N status, and adjuvant therapy were independent prognostic factors for all patients confirmed by multivariate analysis. For patients without PALN metastasis, back pain, tumor size, T status, N status, portal or superior mesenteric vein invasion, and adjuvant therapy were independent prognostic factors, while the only one influence factor for 2‐year OS was adjuvant therapy for patients with metastasis of PALN. Metastasis of PALN was associated with poor prognosis for patients with pancreatic head cancer. Patients with and without metastasis of PALN had different prognostic factors, and adjuvant therapy was the only prognostic factor for patients with metastasis of PALN. Abstract : There were few reports on analysis of prognostic factors for pancreatic head cancer according to para‐aortic lymph node. Different prognostic factors for pancreatic cancer had been confirmed by our study.